Versatile Post‐functionalization of Polyoxometalate Platforms By Using An Unprecedented Range of Palladium‐Catalyzed Coupling Reactions. Issue 38 (28th August 2013) - Lorion, Mélanie M.; Matt, Benjamin; Alves, Sandra; Proust, Anna; Poli, Giovanni; Oble, Julie; Izzet, Guillaume
<x xml:space="preserve">Abstract</x> Handy POMs: Several palladium‐catalyzed coupling reactions have been applied to polyoxometalate post‐functionalization. The feasibility of each reaction with one model substrate was investigated and each set of synthetic conditions was optimized to obtain full conversions and high purity hybrid compounds (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>